Solid electrolyte materials and batteries

By using Li3YX6 type solid electrolyte materials and adjusting the configuration and crystal structure of Y, the problems of low lithium ion conductivity and phase change in the prior art are solved, and the battery has improved its high lithium ion conductivity and safety.

CN115020799BActive Publication Date: 2025-02-28PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210796586.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2017-06-08
Filing Date
2017-07-07
Publication Date
2025-02-28
Estimated Expiration
2037-07-07

AI Technical Summary

Technical Problem

It is difficult to realize solid electrolyte materials with high lithium ion conductivity in the prior art, and there is a phase change problem within the operating temperature range of the battery, which affects the stability and safety of the battery.

Method used

Li3YX6 type solid electrolyte material is used, where X is Cl or Br. By adjusting the configuration and crystal structure of Y, irregular lithium ion conduction paths are formed to avoid phase change, and a variety of crystal phases and amorphous phases are included to improve conductivity.

Benefits of technology

It realizes a stable high lithium ion conductivity within the operating temperature range of the battery, avoids the generation of hydrogen sulfide, and improves the charging and discharging characteristics and safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115020799B_ABST
    Figure CN115020799B_ABST
Patent Text Reader

Abstract

In the prior art, it is desired to realize a solid electrolyte material having high lithium ion conductivity. The solid electrolyte material in one embodiment of the present disclosure is represented by the following composition formula (1). 6‑ 3z Y z X6···Formula (1) Where, 0
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of a Chinese patent application with an application date of July 7, 2017, an application number of 201780011697.4, and an invention title of "Solid Electrolyte Material and Battery". Technical Field

[0002] This disclosure relates to solid electrolyte materials and batteries. Background Art

[0003] Patent Document 1 discloses an all-solid-state battery using a sulfide solid electrolyte.

[0004] Patent Document 2 discloses an all-solid-state battery using an indium-containing halide as a solid electrolyte.

[0005] Prior Art Documents

[0006] Patent Document 1: Japanese Patent Application Laid-Open No. 2011-129312

[0007] Patent Document 2: Japanese Patent Application Laid-Open No. 2006-244734 Summary of the Invention

[0008] In the prior art, it has been desired to realize a solid electrolyte material having a high lithium ion conductivity.

[0009] The solid electrolyte material in one aspect of the present disclosure is represented by the following compositional formula (1).

[0010] Li 6-3z Y z X6…Formula (1)

[0011] Wherein, 0 < z < 2 is satisfied, and X is Cl or Br.

[0012] According to the present disclosure, a solid electrolyte material having a high lithium ion conductivity can be realized. Brief Description of the Drawings

[0013] Figure 1 is a cross-sectional view showing a schematic structure of the battery 1000 in Embodiment 4.

[0014] Figure 2 is a perspective view showing the crystal structure of the Li3ErBr6 structure.

[0015] Figure 3 is a perspective view showing the crystal structure of the Li3ErCl6 structure.

[0016] Figure 4 is a schematic diagram showing a method for evaluating ion conductivity.

[0017] Figure 5It is a graph showing the temperature dependence of the ion conductivity of the solid electrolyte.

[0018] Figure 6 It is a graph showing an XRD pattern of a solid electrolyte material.

[0019] Figure 7 It is a graph showing the initial discharge characteristics.

[0020] Figure 8 It is a three-dimensional diagram showing the crystal structure of Li3YbCl6 structure.

[0021] Fig. 9 It is a graph showing the temperature dependence of the ion conductivity of the solid electrolyte.

[0022] Fig.10 It is a graph showing an XRD pattern of a solid electrolyte material.

[0023] Fig.11 It is a graph showing the initial discharge characteristics.

[0024] Fig.12 It is a graph showing an XRD pattern of a solid electrolyte material. DETAILED DESCRIPTION

[0025] Below, while referring to the attached Figure 1 Embodiments of the present disclosure will be described.

[0026] (Implementation Method 1)

[0027] The solid electrolyte material in Embodiment 1 is a compound represented by the following composition formula (2).

[0028] Li3YX6…Formula (2)

[0029] Wherein, X is Cl (chlorine) or Br (bromine).

[0030] According to the above technical scheme, a solid electrolyte material (halide solid electrolyte material) with high lithium ion conductivity can be realized. In addition, a solid electrolyte material with a stable structure in the assumed operating temperature range of the battery (for example, the range of -30°C to 80°C) can be realized. That is, the solid electrolyte material of embodiment 1 is not a structure in which the phase change temperature exists in the operating temperature range of the battery (for example, the structure of patent document 2). As a result, even in an environment with temperature changes, phase change will not occur in the operating temperature range of the battery, and high ion conductivity can be stably maintained.

[0031] In addition, according to the above technical scheme, an all-solid secondary battery with excellent charge and discharge characteristics can be realized by using the solid electrolyte material of embodiment 1. In addition, a sulfur-free all-solid secondary battery can be realized by using the solid electrolyte material of embodiment 1. That is, the solid electrolyte material of embodiment 1 is not a structure that generates hydrogen sulfide when exposed to the atmosphere (such as the structure of patent document 1). Therefore, an all-solid secondary battery with excellent safety that does not generate hydrogen sulfide can be realized.

[0032] The solid electrolyte material in Embodiment 1 may include a crystal phase. Examples of the crystal phase include the following first crystal phase and second crystal phase.

[0033] That is, the solid electrolyte material in Embodiment 1 may include the first crystal phase.

[0034] In the first crystal phase, the arrangement of X, i.e., halogen, is the same as the arrangement of Br in Li3ErBr6 (hereinafter also referred to as LEB) whose crystal structure belongs to the space group C2 / m.

[0035] According to the above technical solution, a solid electrolyte material with higher lithium ion conductivity can be realized. Specifically, by adopting a crystal structure such as the first crystal phase, X is more strongly attracted to the periphery of Y. Thus, a path for lithium ion diffusion is formed. Therefore, the lithium ion conductivity is further improved.

[0036] Figure 2 It is a three-dimensional diagram showing the crystal structure of Li3ErBr6 structure.

[0037] Li3ErBr6 structure (LEB structure) Figure 2 As shown, it is a crystal structure with monoclinic symmetry and space group C2 / m. Its detailed atomic arrangement is recorded in the Inorganic Crystal Structure Database (ICSD).

[0038] The first crystal phase having the same halogen arrangement as the LEB structure contains two of the above composition formula (2) in the unit cell.

[0039] The lattice constant of the unit cell defined by the LEB structure is α=90°, β=109°, γ=90°.

[0040] The above LEB structure can be identified by structural analysis using X-ray diffraction. and ) as X-rays, when measured by the θ-2θ method, strong peaks were observed in the ranges of diffraction angles 2θ of 25° to 28°, 29° to 32°, 41° to 46°, 49° to 55°, and 51° to 58°, respectively.

[0041] Furthermore, in the solid electrolyte material in Embodiment 1, LEB(110) / I LEB(200) <0.01.

[0042] Among them, I LEB(200) It is the X-ray diffraction intensity of the plane of the first crystal phase corresponding to the (200) plane in the crystal structure of Li3ErBr6.

[0043] In addition, I LEB(110) It is the X-ray diffraction intensity of the plane of the first crystal phase corresponding to the (110) plane in the crystal structure of Li3ErBr6.

[0044] According to the above technical solution, a solid electrolyte material with higher lithium ion conductivity can be realized. Specifically, the configuration of Y can be made irregular. As a result, the lithium ion conduction path is three-dimensionally continuous. Therefore, the lithium ion conductivity is further improved.

[0045] As described above, the arrangement of cations in the solid electrolyte material in Embodiment 1 may be different from the arrangement of cations in the LEB structure. That is, at least a portion of Y (yttrium) and at least a portion of Li may be arranged irregularly.

[0046] The irregularity of the arrangement of cations can be determined by the intensity ratio "I LEB(110) / I LEB(200) " to evaluate.

[0047] When the Y rule is configured, I LEB(110) / I LEB(200) = about 0.02 (about 2%). As the irregularity increases, I LEB(110) / I LEB(200) As mentioned above, if I LEB(110) / I LEB(200) <0.01 (1%), the arrangement of Y can be made sufficiently irregular.

[0048] Furthermore, in the solid electrolyte material in Embodiment 1, FWHM1 / 2θc1≥0.015 can be satisfied.

[0049] Here, FWHM1 is the half-value width of the X-ray diffraction peak of the plane of the first crystal phase corresponding to the (200) plane in the crystal structure of Li3ErBr6.

[0050] In addition, 2θc1 is the diffraction angle of the center of the X-ray diffraction peak (peak center value).

[0051] According to the above technical solution, a solid electrolyte material with higher lithium ion conductivity can be realized. Specifically, the lattice constant can be made non-uniform. Thus, a region with lattice expansion can be formed. Therefore, the lithium ion conductivity is further improved.

[0052] As described above, the lattice constant of the solid electrolyte material in Embodiment 1 may not be completely uniform. That is, the lattice constant may have some non-uniformity. Specifically, the distribution of the lattice constant may have a half-value width of about 1% or more.

[0053] Furthermore, in the solid electrolyte material in Embodiment 1, the structure of the first crystal phase is deformed, and the atomic positions can be arranged in a slightly different arrangement.

[0054] Furthermore, the solid electrolyte material in Embodiment 1 may include a heterogeneous crystal phase having a crystal structure different from that of the first crystal phase.

[0055] At this time, the heterogeneous crystal phase may be interposed between the first crystal phases.

[0056] According to the above technical solution, a solid electrolyte material with higher lithium ion conductivity can be realized. Specifically, the conduction of lithium ions between the first crystal phases can be promoted by the heterogeneous crystal phases. Therefore, the lithium ion conductivity is further improved.

[0057] In addition, the solid electrolyte material in Embodiment 1 may include an amorphous phase.

[0058] At this time, the amorphous phase may be present between the first crystalline phase.

[0059] According to the above technical solution, a solid electrolyte material with higher lithium ion conductivity can be realized. Specifically, the amorphous phase can promote the conduction of lithium ions between the first crystal phases. Therefore, the lithium ion conductivity is further improved.

[0060] Furthermore, the solid electrolyte material in Embodiment 1 may include a second crystal phase.

[0061] In the second crystal phase, the arrangement of X, i.e., halogen, is the same as the arrangement of Cl in Li3ErCl6 (hereinafter also referred to as LEC) whose crystal structure belongs to the space group P-3m1.

[0062] According to the above technical solution, a solid electrolyte material with higher lithium ion conductivity can be realized. Specifically, by adopting a crystal structure such as the second crystal phase, X is more strongly attracted to the periphery of Y. Thus, a path for lithium ion diffusion is formed. Therefore, the lithium ion conductivity is further improved.

[0063] Figure 3 It is a three-dimensional diagram showing the crystal structure of Li3ErCl6 structure.

[0064] Li3ErCl6 structure (LEC structure) Figure 3 As shown, it has a trigonal symmetry and a space group of P-3m1. Its detailed atomic arrangement is recorded in the Inorganic Crystal Structure Database (ICSD).

[0065] The second crystal phase having the same halogen arrangement as the LEC structure contains three of the above composition formula (2) in the unit cell.

[0066] The lattice constant of the unit cell defined by the LEC structure is b=a、 α=90°, β=90°, γ=120°.

[0067] The above LEC structure can be identified by structural analysis using X-ray diffraction. and ) as X-rays, when measured by the θ-2θ method, strong peaks were observed in the ranges of diffraction angles 2θ of 29.8° to 32°, 38.5° to 41.7°, 46.3° to 50.4°, and 50.8° to 55.4°, respectively.

[0068] Furthermore, in the solid electrolyte material in Embodiment 1, LEC(110) / I LEC(303) <0.3.

[0069] Among them, I LEC(303) It is the X-ray diffraction intensity of the plane of the second crystal phase corresponding to the (303) plane in the crystal structure of Li3ErCl6.

[0070] In addition, I LEC(110) It is the X-ray diffraction intensity of the plane of the second crystal phase corresponding to the (110) plane in the crystal structure of Li3ErCl6.

[0071] According to the above technical solution, a solid electrolyte material with higher lithium ion conductivity can be realized. Specifically, the configuration of Y can be made irregular. As a result, the lithium ion conduction path is three-dimensionally continuous. Therefore, the lithium ion conductivity is further improved.

[0072] As described above, the arrangement of cations in the solid electrolyte material in Embodiment 1 may be different from the arrangement of cations in the LEC structure. That is, at least a portion of Y and at least a portion of Li may be arranged irregularly.

[0073] The irregularity of the arrangement of the cations can be seen by the intensity ratio "I LEC(110) / I LEC(303) " to evaluate.

[0074] When the Y rule is configured, it becomes I LEC(110) / I LEC(303) ≥0.45 (about 45%). As the irregularity increases, I LEC(110) / I LEC(303) As mentioned above, if I LEC(110) / I LEC(303) <0.30 (30%), the arrangement of Y can be made sufficiently irregular.

[0075] Furthermore, in the solid electrolyte material in Embodiment 1, FWHM2 / 2θc2≥0.015 can be satisfied.

[0076] Here, FWHM2 is the half-value width of the X-ray diffraction peak of the plane of the second crystal phase corresponding to the (303) plane in the crystal structure of Li3ErCl6.

[0077] In addition, 2θc2 is the diffraction angle (peak center value) at the center of the X-ray diffraction peak.

[0078] According to the above technical solution, a solid electrolyte material with higher lithium ion conductivity can be realized. Specifically, the lattice constant can be made non-uniform. Thus, a region with lattice expansion can be formed. Therefore, the lithium ion conductivity is further improved.

[0079] As described above, the lattice constant of the solid electrolyte material in Embodiment 1 may not be completely uniform. That is, the lattice constant may have some non-uniformity. Specifically, the distribution of the lattice constant may have a half-value width of about 1% or more.

[0080] Furthermore, in the solid electrolyte material in Embodiment 1, the structure of the second crystal phase is deformed, and the atomic positions can be arranged at slightly different positions.

[0081] Furthermore, the solid electrolyte material in Embodiment 1 may include a heterogeneous crystal phase having a crystal structure different from that of the second crystal phase.

[0082] At this time, the heterogeneous crystal phase may be located between the second crystal phases.

[0083] According to the above technical solution, a solid electrolyte material with higher lithium ion conductivity can be realized. Specifically, the conduction of lithium ions between the second crystal phases can be promoted by the heterogeneous crystal phases. Therefore, the lithium ion conductivity is further improved.

[0084] In addition, the solid electrolyte material in Embodiment 1 may include an amorphous phase.

[0085] At this time, the amorphous phase may be interposed between the second crystalline phase.

[0086] According to the above technical solution, a solid electrolyte material with higher lithium ion conductivity can be realized. Specifically, the amorphous phase can promote the conduction of lithium ions between the second crystal phases. Therefore, the lithium ion conductivity is further improved.

[0087] In addition, the shape of the solid electrolyte material in Embodiment 1 is not particularly limited, and may be, for example, needle-shaped, spherical, ellipsoidal, etc. For example, the solid electrolyte material in Embodiment 1 may be particles. After a plurality of particles are stacked, they may be pressed into a granular or plate-like shape.

[0088] For example, when the shape of the solid electrolyte material in Embodiment 1 is a particle shape (for example, a spherical shape), the median diameter may be 0.1 μm or more and 100 μm or less.

[0089] In the first embodiment, the median diameter may be greater than or equal to 0.5 μm and less than or equal to 10 μm.

[0090] According to the above technical solution, the ion conductivity can be further improved. In addition, the solid electrolyte material and the active material in the first embodiment can be in a better dispersed state.

[0091] In the first embodiment, the solid electrolyte material may be smaller than the median diameter of the active material.

[0092] According to the above technical solution, the solid electrolyte material and active material in the first embodiment can be in a better dispersed state.

[0093] <Method for producing solid electrolyte material>

[0094] The solid electrolyte material in Embodiment 1 can be produced, for example, by the following method.

[0095] Prepare raw material powders of binary halides in a mixing ratio of a target composition. For example, when preparing Li3YCl6, prepare LiCl and YCl3 at a molar ratio of 3:1.

[0096] At this time, X in the composition formula (2) can be determined by selecting the type of raw material powder. After the raw material powders are well mixed, the raw material powders are mixed, crushed and reacted by a mechanochemical grinding method. Alternatively, the raw material powders can be well mixed and then sintered in a vacuum.

[0097] Thereby, a solid electrolyte material including the above-mentioned crystal phase can be obtained.

[0098] Furthermore, the structure of the crystal phase (crystal structure) in the solid electrolyte material can be determined by adjusting the reaction method and reaction conditions of the raw material powders.

[0099] (Embodiment 2)

[0100] Hereinafter, Embodiment 2 will be described. Descriptions that overlap with Embodiment 1 described above will be appropriately omitted.

[0101] The solid electrolyte material in Embodiment 2 is a compound represented by the following compositional formula (1).

[0102] Li 6-3z Y z X6…Formula (1)

[0103] Wherein, 0 < z < 2 is satisfied. Moreover, X is Cl or Br.

[0104] According to the above technical solution, a solid electrolyte material (halide solid electrolyte material) having a high lithium ion conductivity can be realized. In addition, a solid electrolyte material having a stable structure within the assumed operating temperature range of the battery (for example, in the range of -30°C to 80°C) can be realized. That is, the solid electrolyte material of Embodiment 2 does not have a structure in which the phase transition temperature exists within the operating temperature range of the battery (for example, the structure of Patent Document 2). Therefore, even in an environment with temperature changes, no phase transition occurs within the operating temperature range of the battery, and a high ion conductivity can be stably maintained.

[0105] In addition, according to the above technical solution, by using the solid electrolyte material of Embodiment 2, a all-solid-state secondary battery with excellent charge and discharge characteristics can be realized. In addition, by using the solid electrolyte material of Embodiment 2, a all-solid-state secondary battery without sulfur can be realized. That is, the solid electrolyte material of Embodiment 2 does not have a structure that generates hydrogen sulfide when exposed to the atmosphere (for example, the structure of Patent Document 1). Therefore, a all-solid-state secondary battery that does not generate hydrogen sulfide and has excellent safety can be realized.

[0106] Furthermore, in the solid electrolyte material of Embodiment 2, 0.75 ≤ z ≤ 1.5 is satisfied.

[0107] According to the above technical solution, a solid electrolyte material (halide solid electrolyte material) having a higher lithium ion conductivity can be realized. In addition, a all-solid-state secondary battery with more excellent charge and discharge characteristics can be realized.

[0108] Furthermore, in the solid electrolyte material of Embodiment 2, 1 ≤ z ≤ 1.25 is satisfied.

[0109] According to the above technical solution, a solid electrolyte material (halide solid electrolyte material) having a higher lithium ion conductivity can be realized. In addition, a all-solid-state secondary battery with more excellent charge and discharge characteristics can be realized.

[0110] Furthermore, the solid electrolyte material in Embodiment 2 may include a crystal phase. Examples of the crystal phase include the following first crystal phase and third crystal phase.

[0111] That is, the solid electrolyte material in Embodiment 2 may include the first crystal phase.

[0112] In the first crystal phase, the arrangement of X, i.e., halogen, is the same as the arrangement of Br in Li3ErBr6 (hereinafter also referred to as LEB) whose crystal structure belongs to the space group C2 / m.

[0113] According to the above technical solution, a solid electrolyte material with higher lithium ion conductivity can be realized. Specifically, by adopting a crystal structure such as the first crystal phase, X is more strongly attracted to the periphery of Y. Thus, a path for lithium ion diffusion is formed. Therefore, the lithium ion conductivity is further improved.

[0114] Li3ErBr6 structure (LEB structure) Figure 2 As shown, it is a crystal structure with monoclinic symmetry and space group C2 / m. Its detailed atomic arrangement is recorded in the Inorganic Crystal Structure Database (ICSD).

[0115] The first crystal phase having the same halogen arrangement as the LEB structure contains two of the above composition formula (1) in the unit cell.

[0116] The lattice constant of the unit cell defined by the LEB structure is α=90°, β=109°, γ=90°.

[0117] The above LEB structure can be identified by structural analysis using X-ray diffraction. and ) as X-rays, when measured by the θ-2θ method, strong peaks were observed in the ranges of diffraction angles 2θ of 25° to 28°, 29° to 33°, 41° to 47°, 49° to 55°, and 51° to 58°, respectively.

[0118] Furthermore, in the solid electrolyte material in the second embodiment, LEB(110) / I LEB(200) <0.01.

[0119] Among them, I LEB(200) It is the X-ray diffraction intensity of the plane of the first crystal phase corresponding to the (200) plane in the crystal structure of Li3ErBr6.

[0120] In addition, I LEB(110) It is the X-ray diffraction intensity of the plane of the first crystal phase corresponding to the (110) plane in the crystal structure of Li3ErBr6.

[0121] According to the above technical solution, a solid electrolyte material with higher lithium ion conductivity can be realized. Specifically, the configuration of Y can be made irregular. As a result, the lithium ion conduction path is three-dimensionally continuous. Therefore, the lithium ion conductivity is further improved.

[0122] As described above, the arrangement of cations in the solid electrolyte material in Embodiment 2 may be different from the arrangement of cations in the LEB structure. That is, at least a part of Y and at least a part of Li may be arranged irregularly.

[0123] The irregularity of the arrangement of the cations can be seen by the intensity ratio "I LEB(110) / I LEB(200) " to evaluate.

[0124] In the case of Y rule configuration, it becomes I LEB(110) / I LEB(200) = about 0.02 (about 2%). As the irregularity increases, I LEB(110) / I LEB(200) As mentioned above, if I LEB(110) / I LEB(200) <0.01 (1%), the arrangement of Y can be made sufficiently irregular.

[0125] Furthermore, in the solid electrolyte material in the second embodiment, FWHM1 / 2θc1≥0.015 can be satisfied.

[0126] Here, FWHM1 is the half-value width of the X-ray diffraction peak of the plane of the first crystal phase corresponding to the (200) plane in the crystal structure of Li3ErBr6.

[0127] In addition, 2θc1 is the diffraction angle of the center of the X-ray diffraction peak (peak center value).

[0128] According to the above technical solution, a solid electrolyte material with higher lithium ion conductivity can be realized. Specifically, the lattice constant can be made non-uniform. Thus, a region with lattice expansion can be formed. Therefore, the lithium ion conductivity is further improved.

[0129] As described above, the lattice constant of the solid electrolyte material in Embodiment 2 may not be completely uniform. That is, the lattice constant may have some non-uniformity. Specifically, the distribution of the lattice constant may have a half-value width of about 1% or more.

[0130] Furthermore, in the solid electrolyte material in the second embodiment, the structure of the first crystal phase is deformed, and the atomic positions can be arranged at slightly different positions.

[0131] Furthermore, the solid electrolyte material in the second embodiment may include a heterogeneous crystal phase having a crystal structure different from that of the first crystal phase.

[0132] At this time, the heterogeneous crystal phase may be interposed between the first crystal phases.

[0133] According to the above technical solution, a solid electrolyte material with higher lithium ion conductivity can be realized. Specifically, the conduction of lithium ions between the first crystal phases can be promoted by the heterogeneous crystal phases. Therefore, the lithium ion conductivity is further improved.

[0134] In addition, the solid electrolyte material in Embodiment 2 may include an amorphous phase.

[0135] At this time, the amorphous phase may be present between the first crystalline phase.

[0136] According to the above technical solution, a solid electrolyte material with higher lithium ion conductivity can be realized. Specifically, the amorphous phase can promote the conduction of lithium ions between the first crystal phases. Therefore, the lithium ion conductivity is further improved.

[0137] Furthermore, the solid electrolyte material in Embodiment 2 may include a third crystal phase.

[0138] In the third crystal phase, the arrangement of X, i.e., halogen, is the same as the arrangement of Cl in Li3YbCl6 (hereinafter also referred to as LYC) whose crystal structure belongs to the space group Pnma.

[0139] According to the above technical solution, a solid electrolyte material with higher lithium ion conductivity can be realized. Specifically, by adopting a crystal structure such as the third crystal phase, X is more strongly attracted to the periphery of Y. Thus, a path for lithium ion diffusion can be formed. Therefore, the lithium ion conductivity is further improved.

[0140] Figure 8 It is a three-dimensional diagram showing the crystal structure of Li3YbCl6 structure.

[0141] Li3YbCl6 structure (LYC structure) Figure 8 As shown, it is a crystal structure with orthorhombic symmetry and space group Pnma. Its detailed atomic arrangement is recorded in the Inorganic Crystal Structure Database (ICSD).

[0142] The third crystal phase having the same halogen arrangement as the LYC structure contains three of the above composition formula (1) in the unit cell.

[0143] The lattice constant of the unit cell defined by the LYC structure is

[0144] The above LYC structure can be identified by structural analysis using X-ray diffraction. and ) as X-rays, when measured by the θ-2θ method, strong peaks were observed in the ranges of diffraction angles 2θ of 29.8° to 32°, 38.5° to 41.7°, 46.3° to 50.4°, and 50.8° to 55.4°, respectively.

[0145] Furthermore, in the solid electrolyte material in the second embodiment, FWHM3 / 2θc3≥0.015 can be satisfied.

[0146] Here, FWHM3 is the half-value width of the X-ray diffraction peak of the plane of the third crystal phase corresponding to the (231) plane in the crystal structure of Li3YbCl6.

[0147] In addition, 2θc3 is the diffraction angle (peak center value) at the center of the X-ray diffraction peak.

[0148] According to the above technical solution, a solid electrolyte material with higher lithium ion conductivity can be realized. Specifically, the lattice constant can be made non-uniform. Thus, a region with lattice expansion can be formed. Therefore, the lithium ion conductivity is further improved.

[0149] As described above, the lattice constant of the solid electrolyte material in Embodiment 2 may not be completely uniform. That is, the lattice constant may have some non-uniformity. Specifically, the distribution of the lattice constant may have a half-value width of about 1% or more.

[0150] Furthermore, in the solid electrolyte material in the second embodiment, the structure of the third crystal phase is deformed, and the atomic positions can be arranged at slightly different positions.

[0151] Furthermore, the solid electrolyte material in the second embodiment may include a heterogeneous crystal phase having a crystal structure different from that of the third crystal phase.

[0152] At this time, the heterogeneous crystal phase is between the third crystal phase.

[0153] According to the above technical solution, a solid electrolyte material with higher lithium ion conductivity can be realized. Specifically, the conduction of lithium ions between the third crystal phases can be promoted by the heterogeneous crystal phases. Therefore, the lithium ion conductivity is further improved.

[0154] In addition, the solid electrolyte material in Embodiment 2 may include an amorphous phase.

[0155] At this time, the amorphous phase may be between the third crystalline phase.

[0156] According to the above technical solution, a solid electrolyte material with higher lithium ion conductivity can be realized. Specifically, the amorphous phase can promote the conduction of lithium ions between the third crystal phases. Therefore, the lithium ion conductivity is further improved.

[0157] In addition, the shape of the solid electrolyte material in Embodiment 2 is not particularly limited, and may be, for example, needle-shaped, spherical, ellipsoidal, etc. For example, the solid electrolyte material in Embodiment 2 may be particles. After a plurality of particles are stacked, they may be formed into a granular or plate-like shape by pressurization.

[0158] For example, when the shape of the solid electrolyte material in Embodiment 2 is a particle shape (for example, a spherical shape), the median diameter may be 0.1 μm or more and 100 μm or less.

[0159] In the second embodiment, the median diameter may be greater than or equal to 0.5 μm and less than or equal to 10 μm.

[0160] According to the above technical solution, the ion conductivity can be further improved. In addition, the solid electrolyte material and the active material in the second embodiment can be in a better dispersed state.

[0161] In the second embodiment, the solid electrolyte material may be smaller than the median diameter of the active material.

[0162] According to the above technical solution, the solid electrolyte material and the active material in the second embodiment can form a better dispersed state.

[0163] <Method for producing solid electrolyte material>

[0164] The solid electrolyte material in the second embodiment can be produced by, for example, the following method.

[0165] Prepare raw material powders of binary halides in a mixing ratio of a target composition. For example, when producing Li3YCl6, prepare LiCl and YCl3 at a molar ratio of 3:1.

[0166] In this case, X in the composition formula (1) can be determined by selecting the type of raw material powder. In addition, the value of "z" in the composition formula (1) can be adjusted by adjusting the mixing ratio of the raw material powder containing Y.

[0167] After the raw material powders are well mixed, they are mixed and crushed by mechanochemical grinding to react with each other. Alternatively, after the raw material powders are well mixed, they can be sintered in a vacuum or inert atmosphere (such as argon atmosphere, nitrogen atmosphere, etc.).

[0168] Thereby, a solid electrolyte material including the above-mentioned crystal phase can be obtained.

[0169] Furthermore, the structure (crystal structure) of the crystal phase in the solid electrolyte material can be determined by adjusting the reaction method and reaction conditions of the raw material powders with respect to each other.

[0170] In addition, the composition of the solid electrolyte material can be determined by, for example, ICP emission spectrometry, inert gas fusion-infrared absorption method, EPMA (Electron Probe micro analyzer) method, or the like.

[0171] (Embodiment 3)

[0172] Hereinafter, Embodiment 3 will be described. Descriptions that are repetitive with the above-described Embodiment 1 or 2 will be appropriately omitted.

[0173] The solid electrolyte material in Embodiment 3 is a compound represented by the following compositional formula (1).

[0174] Li 6-3z Y z X6…Formula (1)

[0175] Among them, 0 < z < 2 is satisfied. Moreover, X is Cl or Br.

[0176] Furthermore, the solid electrolyte material in Embodiment 3 may include a crystal phase. As this crystal phase, the following fourth crystal phase and fifth crystal phase can be cited.

[0177] That is, the solid electrolyte material in Embodiment 3 may include the fourth crystal phase.

[0178] In the fourth crystal phase, X is Br. In addition, in the fourth crystal phase, in the structural analysis using X-ray diffraction method, when Cu-Kα rays (wavelength and ) are used as X-rays and measured by the θ-2θ method, peaks are observed in the range where the value of the diffraction angle 2θ is 13.1° to 14.5°, 26.6° to 28.3°, 30.8° to 32.7°, 44.2° to 47.1°, 52.3° to 55.8°, and 54.8° to 58.5°.

[0179] According to the above technical solution, a solid electrolyte material having a higher lithium ion conductivity can be realized. Specifically, it is considered that the following effects bring about an increase in ion conductivity. That is, by adopting a crystal structure such as the fourth crystal phase, Br is more strongly attracted to the periphery of Y. As a result, a path for lithium ion diffusion can be formed. Therefore, the lithium ion conductivity is further increased.

[0180] Furthermore, in the solid electrolyte material in Embodiment 3, FWHM4 / 2θc4 ≥ 0.015 may be satisfied.

[0181] Here, FWHM4 is the half value width of the X-ray diffraction peak observed in the above-mentioned range of 26.6° to 28.3°.

[0182] In addition, 2θc4 is the diffraction angle (peak center value) at the center of the X-ray diffraction peak.

[0183] According to the above technical solution, a solid electrolyte material with higher lithium ion conductivity can be realized. Specifically, it is believed that the improvement of ion conductivity is brought about by the following effects. That is, the lattice constant can be made non-uniform by the above structure. Thus, a region with lattice expansion can be formed. Therefore, the lithium ion conductivity is further improved.

[0184] Furthermore, in the solid electrolyte material in Embodiment 3, I2 / I1<0.1 may be satisfied. More preferably, I2 / I1<0.01 is satisfied.

[0185] Here, I1 is the intensity of the diffraction peak existing in the above-mentioned range of 26.6° to 28.3°.

[0186] In addition, I2 is the intensity of the diffraction peak in the range of 15.0° to 16.0°. When no peak is confirmed in this range, I2=0.

[0187] According to the above technical solution, a solid electrolyte material with higher lithium ion conductivity can be realized. Specifically, it is believed that the improvement of ion conductivity is brought about by the following effects. That is, the configuration of Y can be made irregular by the above structure. As a result, the conduction path of lithium ions is three-dimensionally continuous. Therefore, the lithium ion conductivity is further improved.

[0188] Furthermore, the solid electrolyte material in the third embodiment may include a heterogeneous crystal phase having a crystal structure different from that of the fourth crystal phase.

[0189] At this time, the heterogeneous crystal phase can be between the fourth crystal phase.

[0190] According to the above technical solution, a solid electrolyte material with higher lithium ion conductivity can be realized. Specifically, it is believed that the improvement of ion conductivity is brought about by the following effects. That is, the conduction of lithium ions between the fourth crystal phase can be promoted through the heterogeneous crystal phase. Therefore, the lithium ion conductivity is further improved.

[0191] In addition, the solid electrolyte material in Embodiment 3 may include an amorphous phase.

[0192] At this time, the amorphous phase may be between the fourth crystalline phase.

[0193] According to the above technical solution, a solid electrolyte material with higher lithium ion conductivity can be realized. Specifically, it is believed that the improvement of ion conductivity is brought about by the following effects. That is, the conduction of lithium ions between the fourth crystal phase can be promoted through the amorphous phase. Therefore, the lithium ion conductivity is further improved.

[0194] In the fifth crystal phase, X is Cl. In the structural analysis of the fifth crystal phase by X-ray diffraction, Cu-Kα rays (wavelength and ) When the X-ray is measured by the θ-2θ method, peaks are observed in the ranges of diffraction angle 2θ of 15.3° to 16.3°, 29.8° to 32°, 38.5° to 41.7°, 46.3° to 50.4°, and 50.8° to 55.4°.

[0195] According to the above technical solution, a solid electrolyte material with higher lithium ion conductivity can be realized. Specifically, it is believed that the improvement of ion conductivity is brought about by the following effects. That is, by adopting a crystal structure such as the fifth crystal phase, Cl is more strongly attracted to the periphery of Y. Thus, a path for lithium ion diffusion can be formed. Therefore, the lithium ion conductivity is further improved.

[0196] Furthermore, in the solid electrolyte material in the third embodiment, FWHM5 / 2θc5≥0.015 can be satisfied.

[0197] Here, FWHM5 is the half value width of the X-ray diffraction peak of the diffraction peak existing at the above-mentioned 29.8° to 32°.

[0198] In addition, 2θc5 is the diffraction angle (peak center value) at the center of the X-ray diffraction peak.

[0199] According to the above technical solution, a solid electrolyte material with higher lithium ion conductivity can be realized. Specifically, it is believed that the improvement of ion conductivity is brought about by the following effects. That is, the lattice constant can be made non-uniform by the above structure. Thus, a region with lattice expansion can be formed. Therefore, the lithium ion conductivity is further improved.

[0200] Furthermore, in the solid electrolyte material in Embodiment 3, I4 / I3<0.3 can be satisfied.

[0201] Here, I3 is the intensity of the diffraction peak existing at the above-mentioned 29.8° to 32°.

[0202] In addition, I4 is the intensity of the diffraction peak existing in the above-mentioned range of 15.3° to 16.3°.

[0203] According to the above technical solution, a solid electrolyte material with higher lithium ion conductivity can be realized. Specifically, it is believed that the improvement of ion conductivity is brought about by the following effects. That is, the configuration of Y can be made irregular by the above structure. As a result, the conduction path of lithium ions is three-dimensionally continuous. Therefore, the lithium ion conductivity is further improved.

[0204] Furthermore, the solid electrolyte material in the third embodiment may include a heterogeneous crystal phase having a crystal structure different from that of the fifth crystal phase.

[0205] At this time, the heterogeneous crystal phase can be between the fifth crystal phase.

[0206] According to the above technical solution, a solid electrolyte material with higher lithium ion conductivity can be realized. Specifically, it is believed that the improvement of ion conductivity is brought about by the following effects. That is, the conduction of lithium ions between the fifth crystal phase can be promoted through the heterogeneous crystal phase. Therefore, the lithium ion conductivity is further improved.

[0207] In addition, the solid electrolyte material in Embodiment 3 may include an amorphous phase.

[0208] At this time, the amorphous phase may be between the fifth crystalline phase.

[0209] According to the above technical solution, a solid electrolyte material with higher lithium ion conductivity can be realized. Specifically, it is believed that the improvement of ion conductivity is brought about by the following effects. That is, the conduction of lithium ions between the fifth crystal phase can be promoted through the amorphous phase. Therefore, the lithium ion conductivity is further improved.

[0210] <Method for producing solid electrolyte material>

[0211] The solid electrolyte material in Embodiment 3 can be produced, for example, by the following method.

[0212] Prepare raw material powders of binary halides in a mixing ratio of a target composition. For example, when producing Li3YCl6, prepare LiCl and YCl3 at a molar ratio of 3:1.

[0213] In this case, by selecting the type of raw material powder, X in the composition formula (1) can be determined. In addition, by adjusting the mixing ratio of the raw material powder containing Y, the value of "z" in the composition formula (1) can be adjusted.

[0214] After the raw material powders are well mixed, the raw material powders are mixed, crushed and reacted by mechanochemical grinding. Alternatively, after the raw material powders are well mixed, they can be sintered in a vacuum or inert atmosphere (such as argon atmosphere, nitrogen atmosphere, etc.).

[0215] Thereby, a solid electrolyte material including the above-mentioned crystal phase can be obtained.

[0216] The structure of the crystal phase in the solid electrolyte material can be determined by powder X-ray diffraction. Powder X-ray diffraction measurement is preferably performed on a sample in an inert atmosphere (eg, argon atmosphere, nitrogen atmosphere, etc.) or in a dry atmosphere with a dew point of -30°C or less.

[0217] (Implementation 4)

[0218] Embodiment 4 will be described below. The description overlapping with any of the above-mentioned Embodiments 1 to 3 will be appropriately omitted.

[0219] The battery in the fourth embodiment is formed using the solid electrolyte material described in any one of the first to third embodiments.

[0220] The battery in the fourth embodiment includes a solid electrolyte material, a positive electrode, a negative electrode, and an electrolyte layer.

[0221] The electrolyte layer is a layer provided between the positive electrode and the negative electrode.

[0222] At least one of the electrolyte layer and the negative electrode contains the solid electrolyte material according to any one of Embodiments 1 to 3.

[0223] According to the above technical solution, the charge and discharge characteristics of the battery can be improved.

[0224] Hereinafter, a specific example of the battery in the fourth embodiment will be described.

[0225] Figure 1 This is a cross-sectional view schematically showing the structure of a battery 1000 in the fourth embodiment.

[0226] The battery 1000 in the fourth embodiment includes a positive electrode 201 , a negative electrode 203 , and an electrolyte layer 202 .

[0227] The positive electrode 201 includes positive electrode active material particles 204 .

[0228] The electrolyte layer 202 is disposed between the positive electrode 201 and the negative electrode 203 .

[0229] The electrolyte layer 202 includes an electrolyte material (eg, a solid electrolyte material).

[0230] The negative electrode 203 includes negative electrode active material particles 205 and solid electrolyte particles 100 .

[0231] The solid electrolyte particle 100 is a particle composed of the solid electrolyte material in any one of Embodiments 1 to 3, or a particle containing the solid electrolyte material in any one of Embodiments 1 to 3 as a main component.

[0232] The positive electrode 201 includes a material having a property of storing and releasing metal ions (for example, lithium ions). The positive electrode 201 includes, for example, a positive electrode active material (for example, positive electrode active material particles 204).

[0233] Positive electrode active materials may include, for example, lithium-containing transition metal oxides (such as Li(NiCoAl)O2, LiCoO2, etc.), transition metal fluorides, polyanions and fluorinated polyanion materials, as well as transition metal sulfides, transition metal fluoride oxides, transition metal sulfur oxides, transition metal nitrogen oxides, etc.

[0234] The median diameter of the positive electrode active material particles 204 may be 0.1 μm or more and 100 μm or less. If the median diameter of the positive electrode active material particles 204 is larger than 100 μm, lithium diffusion in the positive electrode active material particles 204 slows down. As a result, the battery may have difficulty operating at high output.

[0235] The thickness of the positive electrode 201 may be 10 to 500 μm. If the thickness of the positive electrode is thinner than 10 μm, it may be difficult to ensure sufficient battery energy density. If the thickness of the positive electrode is thicker than 500 μm, it may be difficult to operate at high output power.

[0236] The electrolyte layer 202 is a layer containing an electrolyte material. The electrolyte material may be, for example, a solid electrolyte material. That is, the electrolyte layer 202 may be a solid electrolyte layer.

[0237] The solid electrolyte layer may be composed only of the solid electrolyte material of any one of the first to third embodiments.

[0238] Alternatively, it may be composed only of a solid electrolyte material different from the solid electrolyte material in any one of Embodiments 1 to 3. As a solid electrolyte material different from the solid electrolyte material in any one of Embodiments 1 to 3, for example, Li2MgX4, Li2FeX4, Li(Al,Ga,In)X4, Li3(Al,Ga,In)X6, LiI, etc. (X is F, Cl, Br, I) can be used.

[0239] The solid electrolyte layer may contain the solid electrolyte material in any one of embodiments 1 to 3 and a solid electrolyte material different from the solid electrolyte material in any one of embodiments 1 to 3. In this case, both may be uniformly dispersed. The layer composed of the solid electrolyte material in any one of embodiments 1 to 3 and the layer composed of the solid electrolyte material different from the solid electrolyte material in any one of embodiments 1 to 3 may be arranged in sequence relative to the stacking direction of the battery.

[0240] The thickness of the solid electrolyte layer may be greater than 1 μm and less than 100 μm. When the thickness of the solid electrolyte layer is thinner than 1 μm, the possibility of a short circuit between the positive electrode 201 and the negative electrode 203 increases. In addition, when the thickness of the solid electrolyte layer is thicker than 100 μm, it may be difficult to operate at high output power.

[0241] The negative electrode 203 includes a material having the property of storing and releasing metal ions (for example, lithium ions). The negative electrode 203 includes, for example, a negative electrode active material (for example, negative electrode active material particles 205).

[0242] Negative electrode active materials can use metal materials, carbon materials, oxides, nitrides, tin compounds, silicon compounds, etc. The metal material can be a single metal. Alternatively, the metal material can also be an alloy. Examples of metal materials include lithium metal, lithium alloys, etc. Examples of carbon materials include natural graphite, coke, partially graphitized carbon, carbon fiber, spherical carbon, artificial graphite, amorphous carbon, etc. From the viewpoint of capacity density, silicon (Si), tin (Sn), silicon compounds, and tin compounds can be appropriately used. When using a negative electrode active material with a low average reaction voltage, the electrolysis inhibition effect brought about by the solid electrolyte material in any one of embodiments 1 to 3 can be better exerted.

[0243] The median diameter of the negative electrode active material particles 205 can be greater than 0.1 μm and less than 100 μm. If the median diameter of the negative electrode active material particles 205 is smaller than 0.1 μm, the negative electrode active material particles 205 and the solid electrolyte particles 100 may not form a good dispersion state in the negative electrode. As a result, the charge and discharge characteristics of the battery are reduced. In addition, if the median diameter of the negative electrode active material particles 205 is greater than 100 μm, the diffusion of lithium in the negative electrode active material particles 205 slows down. Therefore, it is sometimes difficult to operate the battery at high output power.

[0244] The median diameter of the negative electrode active material particles 205 may be larger than the median diameter of the solid electrolyte particles 100. Thus, the negative electrode active material particles 205 and the halide solid electrolyte material can be well dispersed.

[0245] The volume ratio "v:100-v" of the negative electrode active material particles 205 and the solid electrolyte particles 100 contained in the negative electrode 203 can be 30≤v≤95. When v<30, it may be difficult to ensure sufficient battery energy density. In addition, when v>95, it may be difficult to operate at high output power.

[0246] The thickness of the negative electrode 203 may be greater than 10 μm and less than 500 μm. If the thickness of the negative electrode is thinner than 10 μm, it may be difficult to ensure sufficient battery energy density. In addition, if the thickness of the positive electrode is greater than 500 μm, it may be difficult to operate at high output power.

[0247] At least one of the positive electrode 201, the electrolyte layer 202, and the negative electrode 203 may include a sulfide solid electrolyte and / or an oxide solid electrolyte for the purpose of improving ion conductivity. As the sulfide solid electrolyte, Li2S-P2S5, Li2S-SiS2, Li2S-B2S3, Li2S-GeS2, Li 3.25 Ge 0.25 P 0.75 S4, Li 10 GeP2S 12 As oxide solid electrolytes, NASICON solid electrolytes represented by LiTi2(PO4)3 and its elemental substitutes, (LaLi)TiO3-based perovskite solid electrolytes, and Li 14 ZnGe4O 16 , LISICON solid electrolytes represented by Li4SiO4, LiGeO4 and their elemental substitutes, Li7La3Zr2O 12 Garnet-type solid electrolytes represented by Li3N and its H-substituted products, Li3PO4 and its N-substituted products, etc.

[0248] At least one of the positive electrode 201, the electrolyte layer 202 and the negative electrode 203 may include an organic polymer solid electrolyte for the purpose of improving ion conductivity. As the organic polymer solid electrolyte, a compound such as a polymer compound and a lithium salt may be used. The polymer compound may have an ethylene oxide structure. By having an ethylene oxide structure, it is possible to contain a large number of lithium salts, which can further improve ion conductivity. As lithium salts, LiPF6, LiBF4, LiSbF6, LiAsF6, LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), LiC(SO2CF3)3, etc. may be used. As a lithium salt, one lithium salt selected from the above may be used alone. Alternatively, as a lithium salt, a mixture of two or more lithium salts selected from the above may be used.

[0249] At least one of the positive electrode 201 , the electrolyte layer 202 , and the negative electrode 203 may contain a non-aqueous electrolyte solution, a gel electrolyte, or an ionic liquid in order to facilitate the transfer of lithium ions and thereby improve the output characteristics of the battery.

[0250] The non-aqueous electrolyte solution comprises a non-aqueous solvent and a lithium salt dissolved in the non-aqueous solvent. As the non-aqueous solvent, a cyclic carbonate solvent, a chain carbonate solvent, a cyclic ether solvent, a chain ether solvent, a cyclic ester solvent, a chain ester solvent, a fluorine solvent, etc. can be used. Examples of cyclic carbonate solvents include ethylene carbonate, propylene carbonate, butylene carbonate, etc. Examples of chain carbonate solvents include dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, etc. Examples of cyclic ether solvents include tetrahydrofuran, 1,4-di ... Alkane, 1,3-dioxolane, etc. As chain ether solvents, 1,2-dimethoxyethane, 1,2-diethoxyethane, etc. can be mentioned. As examples of cyclic ester solvents, γ-butyrolactone, etc. can be mentioned. As examples of chain ester solvents, methyl acetate, etc. can be mentioned. As examples of fluorinated solvents, fluoroethylene carbonate, methyl fluoropropionate, fluorobenzene, methyl ethyl fluorocarbonate, dimethyl fluorocarbonate, etc. can be mentioned. As non-aqueous solvents, one non-aqueous solvent selected from them can be used alone. Alternatively, as non-aqueous solvents, two or more non-aqueous solvents selected from them can be used in combination. The non-aqueous electrolyte can contain at least one fluorinated solvent selected from fluoroethylene carbonate, methyl fluoropropionate, fluorobenzene, methyl ethyl fluorocarbonate, and dimethyl fluorocarbonate. As the lithium salt, LiPF6, LiBF4, LiSbF6, LiAsF6, LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), LiC(SO2CF3)3, etc. can be used. As the lithium salt, one lithium salt selected from them can be used alone. Alternatively, as the lithium salt, a mixture of two or more lithium salts selected from them can be used. The concentration of the lithium salt is, for example, in the range of 0.5 to 2 mol / liter.

[0251] The gel electrolyte may be an electrolyte containing a non-aqueous electrolyte in a polymer material. As the polymer material, polyethylene oxide, polyacrylonitrile, polyvinylidene fluoride, polymethyl methacrylate, a polymer having an ethylene oxide bond, or the like may be used.

[0252] The cations constituting the ionic liquid may be aliphatic chain quaternary salts such as tetraalkylammonium and tetraalkylphosphonium, pyrrolidone Morpholine Imidazolin Tetrahydropyrimidine Piperazine Piperidine Aliphatic cyclic ammonium, pyridine, etc. Imidazole The anions that constitute the ionic liquid can be PF6-, BF4-, SbF6 - 、AsF6 - 、SO3CF3- 、N(SO2CF3)2 - 、N(SO2C2F5)2 - , N(SO2CF3)(SO2C4F9)-, C(SO2CF3)-, etc. In addition, the ionic liquid may contain a lithium salt.

[0253] For the purpose of improving the adhesion between particles, at least one of the positive electrode 201, the electrolyte layer 202 and the negative electrode 203 may include a binder. The binder is used to improve the adhesion of the material constituting the electrode. As a binder, polyvinylidene fluoride, polytetrafluoroethylene, polyethylene, polypropylene, aramid resin, polyamide, polyimide, polyamide-imide, polyacrylonitrile, polyacrylic acid, polymethyl acrylate, polyethyl acrylate, polyhexyl acrylate, polymethacrylic acid, polymethyl methacrylate, polyethyl methacrylate, polyhexyl methacrylate, polyvinyl acetate, polyvinyl pyrrolidone, polyether, polyether sulfone, hexafluoropolypropylene, styrene butadiene rubber, carboxymethyl cellulose, etc. can be cited. In addition, as a binder, a copolymer of two or more materials selected from tetrafluoroethylene, hexafluoroethylene, hexafluoropropylene, perfluoroalkyl vinyl ether, vinylidene fluoride, trifluorochloroethylene, ethylene, propylene, pentafluoropropylene, fluoromethyl vinyl ether, acrylic acid, and hexadiene can be used. In addition, two or more selected from these may be mixed and used as a binder.

[0254] In addition, at least one of the positive electrode 201 and the negative electrode 203 may contain a conductive auxiliary agent as necessary.

[0255] The conductive additive is used to reduce the electrode resistance. As the conductive additive, graphite such as natural graphite or artificial graphite, carbon black such as acetylene black and Ketjen black, conductive fibers such as carbon fiber or metal fiber, metal powders such as carbon fluoride and aluminum, conductive whiskers such as zinc oxide or potassium titanate, conductive metal oxides such as titanium oxide, polyaniline, polypyrrole, polythiophene, etc. can be cited. Furthermore, as the conductive additive, by using a carbon conductive additive, low cost can be sought.

[0256] The battery in the fourth embodiment can be configured as a battery in various shapes such as a coin-shaped, cylindrical, square, sheet-shaped, button-shaped, flat, or laminated type.

[0257] Example

[0258] Hereinafter, the details of the present disclosure will be described using Examples and Comparative Examples.

[0259] 《Example A1》

[0260] [Production of solid electrolyte materials]

[0261] In a dry atmosphere with a dew point of -30°C or less, raw material powders LiBr and YBr3 were weighed so that the molar ratio of LiBr:YBr3=3:1. These were ground and mixed in a mortar. Thereafter, a planetary ball mill was used to perform a grinding process at 600 rpm for 25 hours.

[0262] Through the above treatment, a powder of the solid electrolyte material of Example A1, namely Li3YBr6, containing a crystal phase was obtained.

[0263] [Evaluation of ion conductivity]

[0264] Figure 4 It is a schematic diagram showing the evaluation method of ion conductivity.

[0265] The press-molding die 300 is composed of a frame die 301 made of electronically insulating polycarbonate, and an upper punch 303 and a lower punch 302 made of electronically conductive stainless steel.

[0266] use Figure 4 The ion conductivity of the structure shown was evaluated by the following method.

[0267] In a dry atmosphere with a dew point of -30°C or less, the powder of the solid electrolyte material of Example A1 was filled into a press-forming die 300 and uniaxially pressed at 400 MPa to produce a conductivity measurement cell of Example A1.

[0268] Under pressure, the lead wires were taken out from the punch upper part 303 and the punch lower part 302, respectively, and connected to a potentiostat (VersaSTAT4, Princeton Applied Research) equipped with a frequency response analyzer, and the ion conductivity was measured at room temperature using electrochemical impedance spectroscopy.

[0269] The ionic conductivity of the solid electrolyte material of Example A1 measured at 22°C was 3.0×10 -4 S / cm.

[0270] [Evaluation of phase transition]

[0271] Figure 5 It is a graph showing the temperature dependence of the ion conductivity of the solid electrolyte.

[0272] Figure 5 The results shown were determined using the following method.

[0273] Specifically, the conductivity measurement cell of Example A1 was placed in a thermostatic chamber, and the temperature dependency of the conductivity was measured in a temperature increase process and a temperature decrease process within a range of -30°C to 80°C.

[0274] like Figure 5 As shown, no sharp change in conductivity indicating a phase change (phase transition) is observed.

[0275] [Analysis of crystal structure]

[0276] Figure 6 : is a graph showing an XRD pattern of a solid electrolyte material. Peaks were observed at positions where the 2θ values ​​were 13.7°, 27.4°, 31.7°, 45.5°, 54.0°, and 56.6°.

[0277] Figure 6 The results shown were determined using the following method.

[0278] Specifically, the crystal structure analysis of the solid electrolyte was performed using an X-ray diffraction device (Rigaku MiniFlex600) to measure the X-ray diffraction pattern in a dry environment with a dew point of -45° C. or less. Cu—Kα rays were used as the X-ray source.

[0279] The obtained X-ray diffraction pattern of the solid electrolyte material of Example A1 was analyzed. As a result, the X-ray diffraction pattern at lattice constants a=6.93, b=11.96, c=6.84, α=90°, β=109°, and γ=90° in a crystal structure with the same anion arrangement as the LEB structure was formed, which was consistent with the X-ray diffraction pattern of the solid electrolyte material of Example A1.

[0280] The diffraction intensity near the diffraction peak corresponding to the (200) plane of the LEB structure (I LEB(200) ), and the diffraction peak intensity corresponding to the (110) plane (I LEB(110) ) ratio (I LEB(110) / I LEB(200) ) is less than 1%.

[0281] The relationship between the half-value width (FWHM) of the diffraction peak (2θ=27.4°) corresponding to the (200) plane of the LEB structure and the peak center value 2θc is FWHM / 2θc=2.3%.

[0282] [Manufacturing of Secondary Batteries]

[0283] In an argon-filled glove box, the solid electrolyte material Li3YBr6 of Example A1 and LiCoO2 (hereinafter referred to as LCO) as an active material were weighed at a volume ratio of 50:50 and mixed in an agate mortar to prepare a mixture.

[0284] The solid electrolyte material of Example A1 in an amount corresponding to a thickness of 700 μm and 12.3 mg of the above-mentioned mixture were sequentially stacked in the insulating outer cylinder, and the mixture was press-molded at a pressure of 360 MPa to obtain a first electrode and a solid electrolyte layer.

[0285] Next, metal In (thickness 200 μm) was stacked on the side of the solid electrolyte layer opposite to the side in contact with the first electrode, and this was press-formed at a pressure of 80 MPa to produce a stacked body consisting of the first electrode, the solid electrolyte layer, and the second electrode.

[0286] Next, stainless steel current collectors were placed above and below the stacked body, and current collecting springs were attached to the current collectors.

[0287] Finally, an insulating ferrule is used to seal the inside of the insulating outer cylinder from the outside atmosphere.

[0288] Through the above-described processes, a secondary battery of Example A1 was produced.

[0289] [Charge and discharge test]

[0290] Figure 7 It is a graph showing the initial discharge characteristics.

[0291] Figure 7 The results shown were determined using the following method.

[0292] That is, the secondary battery of Example A1 was placed in a constant temperature chamber at 25°C.

[0293] Constant current charging was performed at a current value of 0.05C rate (20 hour rate) relative to the theoretical capacity of the battery, and charging was terminated at a voltage of 3.7V.

[0294] Next, the battery was discharged at a current value of 0.05C rate in the same manner, and the discharge was terminated at a voltage of 1.9V.

[0295] According to the above measurement results, the initial discharge capacity of the secondary battery of Example A1 was 126 μAh.

[0296] 《Example A2》

[0297] As raw material powders of the solid electrolyte, LiCl and YCl3 were used and mixed at a molar ratio of LiCl:YCl3=3:1. Thus, Li3YCl6 as the solid electrolyte material of Example A2 was obtained.

[0298] Except for the above, respective evaluations and analyses were carried out in the same manner as in Example A1.

[0299] The ionic conductivity measured at 22°C was 1.1×10 -4 S / cm.

[0300] According to the temperature dependence of conductivity, no phase change is observed in the range of -30°C to 80°C.

[0301] The XRD pattern of the solid electrolyte material of Example A2 is shown in the above Figure 6 Peaks were observed at 2θ values ​​of 15.8°, 31.4°, 40.9°, 48.7°, and 53.6°.

[0302] The obtained X-ray diffraction pattern was analyzed, and the results showed that the X-ray diffraction pattern was consistent with the lattice constants a=11.202, b=11.202, c=6.032, α=90°, β=90°, and γ=120° in a crystal structure with the same anion arrangement as the LEC structure.

[0303] The diffraction intensity near the diffraction peak corresponding to the (303) surface of the LEC structure (I LEC(303) ), and the diffraction peak intensity corresponding to the (110) plane (I LEC(110) ) ratio (I LEC(110) / I LEC(303) ) is 26%.

[0304] The relationship between the half-value width (FWHM) of the diffraction peak (2θ=31.4°) corresponding to the (303) plane of the LEC structure and the peak center value 2θc is FWHM / 2θc=1.8%.

[0305] In addition, as a solid electrolyte used for the mixture and the solid electrolyte layer, the solid electrolyte material of Example A2 was used.

[0306] Except for the above, a secondary battery was produced and a charge and discharge test was carried out in the same manner as in Example A1.

[0307] The initial discharge capacity of the secondary battery of Example A2 was 70 μAh.

[0308] Comparative Example 1

[0309] In a dry atmosphere with a dew point of -30°C or less, raw material powders LiBr and InBr3 were weighed in a molar ratio of LiBr:InBr3=3:1. They were crushed and mixed in a mortar. Thereafter, the sample formed into pellets by pressure was vacuum-sealed in a glass tube and sintered at 200°C for one week.

[0310] Through the above treatment, Li3InBr6 as the solid electrolyte material of Comparative Example 1 was obtained.

[0311] Except for this, the ion conductivity and the phase change were evaluated by the same method as in Example A1.

[0312] The ionic conductivity measured at 22°C is less than 1×10 -7 S / cm.

[0313] The temperature dependence of the ion conductivity of the solid electrolyte material of Comparative Example 1 is shown in the above Figure 5 .

[0314] like Figure 5 As shown, due to the temperature dependence of the conductivity, the conductivity changes rapidly at around 55° C. during the temperature increase process. That is, in the solid electrolyte material of Comparative Example 1, a phase change occurs.

[0315] Comparative Example 2

[0316] As raw material powders of the solid electrolyte, LiCl and FeCl2 were used and mixed at a molar ratio of LiCl:FeCl2 = 2: 1. Thus, Li2FeCl4 as a solid electrolyte material of Comparative Example 2 was obtained.

[0317] The ion conductivity was evaluated in the same manner as in Example A1 except for the above.

[0318] The measured ionic conductivity is 8.7×10 -6 S / cm.

[0319] In addition, as the solid electrolyte used for the mixture and the solid electrolyte layer, the solid electrolyte material of Comparative Example 2 was used.

[0320] Except for the above, a secondary battery was produced and a charge and discharge test was carried out in the same manner as in Example A1.

[0321] The initial discharge characteristics of the secondary battery of Comparative Example 2 are shown in the above Figure 7 .

[0322] The initial discharge capacity of the secondary battery of Comparative Example 2 was less than 1 μAh. That is, the charge and discharge operation of the secondary battery of Comparative Example 2 could not be confirmed.

[0323] Table 1 shows the structures and evaluation results of Examples A1 and A2 and Comparative Examples 1 and 2.

[0324] [Table 1]

[0325]

[0326] Investigation

[0327] Comparing Examples A1 and A2 with Comparative Example 1, it can be seen that Li3YX6 does not undergo phase change in the range of -30°C to 80°C. In other words, it can be seen that Examples A1 and A2 are structurally stable in the assumed operating temperature range of the battery.

[0328] In addition, when comparing Examples A1 and A2 and Comparative Examples 1 and 2, it can be seen that Li3YX6 shows a 1×10 -5High ion conductivity of more than S / cm.

[0329] In addition, in both Examples A1 and A2, the battery charge and discharge operation was shown at room temperature. On the other hand, in Comparative Example 2, the discharge capacity was hardly obtained and the battery operation could not be confirmed.

[0330] 《Examples B1 to B8》

[0331] Next, for Li 6-3z Y z The synthesis and evaluation methods of Br6 are described.

[0332] [Production of solid electrolyte materials]

[0333] In a glove box maintained in a dry low-oxygen atmosphere with a dew point of -90°C or less and an oxygen value of 5 ppm or less, raw material powders LiBr and YBr3 were weighed so that the molar ratio of LiBr:YBr3=6-3z:z.

[0334] The "value of z" of each of Examples B1 to B8 is shown in Table 2 described later.

[0335] Except for these, the solid electrolyte materials of Examples B1 to B8 were prepared in the same manner as in Example A1.

[0336] [Evaluation of ion conductivity]

[0337] In a glove box maintained in a dry low-oxygen atmosphere with a dew point of -90°C or less and an oxygen value of 5 ppm or less, conductivity measurement cells of Examples B1 to B8 were prepared by the same method as in Example A1.

[0338] The ion conductivity was measured in the same manner as in Example A1 except for the above.

[0339] [Evaluation of phase transition]

[0340] The conductivity measurement cells of Examples B1 to B8 were placed in a thermostatic chamber and the temperature dependence of the conductivity was measured in a temperature increase process and a temperature decrease process in the range of -30°C to 80°C. As a result, no abrupt change in conductivity indicating a phase change was observed in any of the Examples.

[0341] Fig. 9 It is a graph showing the temperature dependence of the ion conductivity of the solid electrolyte.

[0342] Fig. 9 As a typical example, the temperature dependence of the ion conductivity of "z=1" (ie, Li3YBr6) as Example B3 is shown.

[0343] [Analysis of crystal structure]

[0344] The crystal structure of each of the solid electrolyte materials of Examples B1 to B8 was analyzed by the same method as that of Example A1.

[0345] The X-ray diffraction patterns obtained for the solid electrolyte materials of Examples B1 to B8 were analyzed. As a result, it was determined that all Examples B1 to B8 had a crystal structure in which anions were arranged in the same manner as the LEB structure. In addition, in Example B3, "z = 1" (i.e., Li3YBr6), the X-ray diffraction pattern and the lattice constant The X-ray diffraction patterns at α=90°, β=109°, and γ=90° are consistent.

[0346] Fig.10 It is a graph showing an XRD pattern of a solid electrolyte material.

[0347] Fig.10 As a typical X-ray diffraction pattern, the pattern of "z=1" (i.e., Li3YBr6) of Example B3 is shown. Peaks were observed at positions where the 2θ values ​​were 13.7°, 27.4°, 31.7°, 45.5°, 54.0°, and 56.6°.

[0348] The relationship between the half width FWHM and the peak center 2θc in the LEB (200) diffraction peak (2θ=28°) is shown in Table 2. In all of Examples B1 to B8, FWHM / 2θc≥0.015.

[0349] [Manufacturing of Secondary Batteries]

[0350] In a glove box maintained in a dry low-oxygen atmosphere with a dew point of -90°C or less and an oxygen value of 5 ppm or less, the solid electrolyte material of Examples B1 to B8 and LiCoO2 as an active material were weighed at a volume ratio of 50:50. They were mixed in an agate mortar to prepare the mixtures of Examples B1 to B8.

[0351] Secondary batteries of Examples B1 to B8 were prepared in the same manner as in Example A1 except for the above.

[0352] [Charge and discharge test]

[0353] The charge and discharge test of each of the secondary batteries of Examples B1 to B8 was carried out in the same manner as in Example A1.

[0354] Fig.11 It is a graph showing the initial discharge characteristics.

[0355] Fig.11As a representative initial discharge characteristic, the initial discharge characteristic of "z=1" (ie, Li3YBr6) as Example B3 is shown.

[0356] Table 2 shows the structures and evaluation results of Examples B1 to B8.

[0357] [Table 2]

[0358]

[0359] 《Examples C1 to C8》

[0360] Next, for Li 6-3z Y z The synthesis and evaluation methods of Cl6 are described.

[0361] [Production of solid electrolyte materials]

[0362] In a glove box maintained in a dry low-oxygen atmosphere with a dew point of -90°C or less and an oxygen value of 5 ppm or less, raw material powders LiCl and YCl3 were weighed so that the molar ratio of LiCl:YCl3=6-3z:z.

[0363] The "value of z" of each of Examples C1 to C8 is shown in Table 3 described later.

[0364] Except for the above, the solid electrolyte materials of Examples C1 to C8 were prepared in the same manner as in Example A1.

[0365] [Evaluation of ion conductivity]

[0366] In a glove box maintained in a dry low-oxygen atmosphere with a dew point of -90°C or less and an oxygen value of 5 ppm or less, conductivity measurement cells of Examples C1 to C8 were prepared by the same method as in Example A1.

[0367] The ion conductivity was measured in the same manner as in Example A1 except for the above.

[0368] [Evaluation of phase transition]

[0369] The conductivity measurement cells of Examples C1 to C8 were placed in a thermostatic chamber and the temperature dependence of the conductivity was measured in a temperature increase process and a temperature decrease process in the range of -30°C to 80°C. As a result, no abrupt change in conductivity indicating a phase change was observed in any of the Examples.

[0370] Fig. 9 As a typical example, the temperature dependence of the ion conductivity of "z=1" (ie, Li3YCl6) as Example C3 is shown.

[0371] [Analysis of crystal structure]

[0372] The crystal structure of each of the solid electrolyte materials of Examples C1 to C8 was analyzed by the same method as that of Example A1.

[0373] The X-ray diffraction patterns obtained for the solid electrolyte materials of Examples C1 to C8 were analyzed. As a result, it was determined that all Examples C1 to C8 had a crystal structure in which anions were arranged in the same manner as the LYC structure. In addition, in Example C3, "z = 1" (i.e., Li3YCl6), the X-ray diffraction pattern and the lattice constant (lattice constant of the unit cell defined by the LYC structure) were The X-ray diffraction patterns at α=90°, β=90°, and γ=90° are consistent.

[0374] Fig.12 It is a graph showing an XRD pattern of a solid electrolyte material.

[0375] Fig.12 As a typical X-ray diffraction pattern, the pattern of "z=1" (i.e., Li3YCl6) of Example C3 is shown. Peaks were observed at positions where the 2θ values ​​were 15.8°, 31.2°, 40.7°, 48.6°, and 53.4°.

[0376] The relationship between the half width FWHM and the peak center 2θc in the LYC (231) diffraction peak is shown in Table 3. In all of Examples C1 to C8, FWHM / 2θc ≥ 0.015.

[0377] [Manufacturing of Secondary Batteries]

[0378] In a glove box maintained in a dry low-oxygen atmosphere with a dew point of -90°C or less and an oxygen value of 5 ppm or less, the solid electrolyte material of Examples C1 to C8 and LiCoO2 as an active material were weighed at a volume ratio of 50:50 and mixed in an agate mortar to prepare mixtures of Examples C1 to C8.

[0379] Secondary batteries of Examples C1 to C8 were prepared in the same manner as in Example A1 except for the above.

[0380] [Charge and discharge test]

[0381] The charge and discharge test of each of the secondary batteries of Examples C1 to C8 was carried out in the same manner as in Example A1.

[0382] Fig.11 As a representative initial discharge characteristic, the initial discharge characteristic of "z=1" (ie, Li3YCl6) of Example C3 is shown.

[0383] Table 3 shows the structures and evaluation results of Examples C1 to C8.

[0384] [Table 3]

[0385]

[0386] <<Investigation>>

[0387] Comparing Examples B1 to B8 and C1 to C8 with Comparative Example 1, it can be seen that Examples B1 to B8 and C1 to C8 do not undergo phase change in the range of -30°C to 80°C. In other words, it can be seen that Examples B1 to B8 and C1 to C8 have stable structures in the assumed operating temperature range of the battery.

[0388] In addition, when comparing Examples B1 to B8 and C1 to C8 and Comparative Examples 1 and 2, it can be seen that Examples B1 to B8 and C1 to C8 show 1×10 -5 High ion conductivity of more than S / cm.

[0389] In all of Examples B1 to B8 and C1 to C8, the battery charge and discharge operation was shown at room temperature. On the other hand, in Comparative Example 2, the discharge capacity was hardly obtained and the battery operation could not be confirmed.

[0390] In addition, when comparing Examples B2 to B7 and C2 to C7 and Examples B1, B8, C1, and C8, it can be seen that Examples B2 to B7 and C2 to C7 show 1×10 -4 High ion conductivity of S / cm or more From this, it can be seen that by satisfying 0.75≤z≤1.5, higher ion conductivity is exhibited.

[0391] In addition, when comparing Examples B3 to B5 and C3 to C5 with Examples B1, B2, B6 to B8, C1, C2, and C6 to C8, it can be seen that Examples B3 to B5 and C3 to C5 show 3×10 -4 High ion conductivity of S / cm or more From this, it can be seen that by satisfying 1≤z≤1.25, higher ion conductivity is exhibited.

[0392] As described above, the solid electrolyte material disclosed in the present invention is an electrolyte material that does not generate hydrogen sulfide and can stably maintain high lithium ion conductivity, and can also realize an all-solid-state battery that does not generate hydrogen sulfide and has excellent charge and discharge characteristics.

[0393] Industrial Applicability

[0394] The battery disclosed herein can be used as, for example, an all-solid lithium secondary battery.

[0395] Description of Reference Numerals

[0396] 100 Solid Electrolyte Particles

[0397] 201 Positive electrode

[0398] 202 electrolyte layer

[0399] 203 Negative electrode

[0400] 204 Positive electrode active material particles

[0401] 205 Negative electrode active material particles

[0402] 300 Pressing mold

[0403] 301 frame mold

[0404] 302 Punch lower part

[0405] 303 Punch upper part

[0406] 1000 Batteries

Claims

1. A solid electrolyte material represented by the following composition formula (1): Li 6-3z Y z X6... Formula (1) in, Satisfy 0 <z<2, X is Cl or Br, The solid electrolyte material comprises a third crystal phase, In the third crystal phase, the arrangement of X is the same as the arrangement of Cl in Li3YbCl6 whose crystal structure belongs to the space group Pnma. The half width of the X-ray diffraction peak of the plane of the third crystal phase corresponding to the (231) plane in the crystal structure of Li3YbCl6 is set to FWHM3, The diffraction angle at the center of the X-ray diffraction peak is set to 2θc3. Satisfies FWHM3 / 2θc3≥0.

015. 2 . The solid electrolyte material according to claim 1 , satisfying 0.75≤z≤1.

5. The solid electrolyte material according to claim 2 , satisfying 1≤z≤1.

25.

4. The solid electrolyte material according to any one of claims 1 to 3, comprising a heterogeneous crystal phase having a crystal structure different from that of the third crystal phase, And the heterogeneous crystal phase is between the third crystal phase.

5. The solid electrolyte material according to any one of claims 1 to 3, comprising an amorphous phase, The amorphous phase is between the third crystalline phases.

6. The solid electrolyte material according to any one of claims 1 to 3, wherein X is Br, Contains the 4th phase, The fourth crystalline phase is obtained by X-ray diffraction at a wavelength of and When Cu-Kα rays are used as X-rays for measurement by the θ-2θ method, a crystal phase with peaks is observed in the ranges of diffraction angles 2θ of 13.1° to 14.5°, 26.6° to 28.3°, 30.8° to 32.7°, 44.2° to 47.1°, 52.3° to 55.8°, and 54.8° to 58.5°.

7. The solid electrolyte material according to claim 6, wherein the half width of the X-ray diffraction peak observed in the range of 26.6° to 28.3° in the X-ray diffraction measurement using the Cu-Kα ray is defined as FWHM4, The diffraction angle at the center of the X-ray diffraction peak is set to 2θc4. At this time, Satisfies FWHM4 / 2θc4≥0.

015.

8. The solid electrolyte material according to claim 6, wherein the intensity of the diffraction peak existing in the range of 26.6° to 28.3° in the X-ray diffraction measurement using the Cu-Kα ray is defined as I1, and the intensity of the diffraction peak existing in the range of 15.0° to 16.0° is defined as I2, and in this case, Satisfies I2 / I1<0.

01.

9. The solid electrolyte material according to claim 6, comprising a heterogeneous crystal phase having a crystal structure different from that of the fourth crystal phase, And the heterogeneous crystal phase is between the fourth crystal phase.

10. The solid electrolyte material according to claim 6, comprising an amorphous phase, The amorphous phase is between the fourth crystalline phase.

11. A battery comprising: The solid electrolyte material according to any one of claims 1 to 10, positive electrode, Negative electrode, and An electrolyte layer is provided between the positive electrode and the negative electrode, At least one of the negative electrode and the electrolyte layer contains the solid electrolyte material.

Citation Information

Patent Citations

  • All-solid lithium secondary battery

    JP2006244734A

  • Method of manufacturing sulfide solid electrolyte material, sulfide solid electrolyte material, and lithium battery

    JP2011129312A

  • Ion-conducting glass ceramic having garnet-like crystal structure

    WO2015110385A1